Gerakan Bersih Kampus: Upaya Menumbuhkan Kepedulian Mahasiswa Terhadap Lingkungan - Asnal Mala Mala; Salsabila Fridiana; Rahayu Mardikaningsih; Mufaizah; Mila Hariani (Institut Agama Islam Sunan Giri Ponorogo, 2026)
Environmental activities are an important factor influencing the level of student participation in various cleanliness activities, especially when these activities are also directed as a form of community service. Environmental cleanliness activities aim to strengthen the relationship between the level of environmental awareness of students at Sunan Giri University of Surabaya and their participation in environmental cleanliness programs, which include river cleaning, roadside cleaning, and campus yard arrangement through the mini-state concept. The method used is Participatory Action Research (PAR) through activity participation, activity documentation, and assessment of the level of student involvement. Students with higher levels of environmental awareness tend to have more active participation in cleanliness activities, both in physical aspects such as area cleaning and in creative aspects such as the arrangement of ornamental plants, medicinal plants, and environmental decoration. The conclusion shows that cleanliness activities have also proven to be an effective form of community service because they provide a direct impact on the sustainability of cleanliness in the campus environment and its surroundings.